Peran Bimbingan Konseling Islam dalam Menangani Permasalahan Kesehatan Mental Siswa SMA - Mutiah Muslimah; Widya Hartati; Intan Dian Saputri; khairunnisa, Nur Afifah; Arum Khairun Nisa; Mahasri Shobabiya (Program Studi Pendidikan Agama Islam IAIQI Al-Qur'an Al-Ittifaqiyah, 2024)
This research aims to describe the role of BKI in dealing with the mental health of high school students. This research method uses literature study, by analyzing various literature related to Islamic counseling guidance and Islamic psychological theories that can be applied in an educational context. This study uses sociological and interpretive methods and the research subject in the literature study is literature material. The results of this research show that the impact on students' mental health is such as; stress, anxiety, depression, and even sleep disorders. However, the Islamic Guidance and Counseling (BKI) approach has proven effective in helping students overcome these problems through the integration of biological, psychological, social and spiritual aspects. With approaches such as dhikr, prayer, tazkiyatun nafs, as well as strengthening the values ​​of patience and trust, students are able to manage emotions, increase mental resilience, and cope better with academic pressure. BKI's holistic approach and based on Islamic values ​​also helps students find a balance between academic, social and spiritual, thereby strengthening relationships with family, friends and Allah SWT. This proves that the application of BKI not only provides solutions to students' mental health problems, but also shapes their character and maturity in facing various life challenges. The results of this research indicate that an Islamic-based counseling guidance approach can be an effective solution for overcoming mental health problems among high school students.